THU0368 Are anti-phosphatidylserine prothrombin antibodies a useful screening tool for the lupus anticoagulant?. (12th June 2018) - Pham, M.M.; Orsolini, G.; Crowson, C.S.; Snyder, M.R.; Pruthi, R.K.; Moder, K.G.
Abstract : Background: Anti-phosphatidylserine prothrombin antibodies (PSPT) have been reported to be strongly associated with the lupus anticoagulant (LAC) in established antiphospholipid syndrome (APS) and autoimmune cohorts. However, there is a paucity of similar studies assessing clinical utility on an all-comer patient population undergoing evaluation for suspicions of APS. Objectives: To determine the sensitivity and specificity of IgG and IgM PSPT to the LAC in patients undergoing evaluation for APS. Methods: Patients from June 2017 to December 2017 undergoing evaluation for APS had blood draws for the LAC, anti-cardiolipin (aCL), anti-β2 glycoprotein-1 (β2GP1), and PSPT. Both IgG and IgM isotypes were tested for each antibody. Presence of the LAC was determined by trained haematologists interpreting a number of mixing and neutralisation studies. Demographic details were abstracted from the medical record and cases meeting the SLICC criteria for systemic lupus erythematosus (SLE) and the revised Sapporo criteria for APS were enumerated. Results: Fifty six eligible patients were identified. Mean age was 50±18 years. 68% were female, 20% with SLE, and 20% with APS. At time of testing, 18% were on warfarin, 7% on direct factor Xa inhibitors and 2% on low-molecular weight heparin. The LAC was negative in 45% (25/56) of those tested. In LAC negative cases, the IgG and IgM PSPT were negative in 100% and 92% of cases, respectively. In LAC positive cases, IgG PSPT was positive in 35% and IgM PSPT was positive in 61%. Compared to the LAC, IgG PSPT was 100% (95% CI: 72%, 100%) sensitive but was only 56% (40%, 70%) specific. Similarly, the IgM isotype of PSPT showed 90% (70%, 99%) sensitivity but only 66% (48%, 81%) specificity. Overall, 38% (21/56) of the cases possessed an isolated, singly positive LAC with concurrent negative IgG/M aCL and β2GP1 antibodies. In this isolated LAC positive-only group, further testing with IgG and IgM PSPT was positive in 38% and 57% of the cases, respectively. Conclusions: In this study, IgG and IgM PSPT were found to be highly sensitive to the LAC and may be a useful tool in the screening of and the interpretation of the LAC. References: [1] Akhter E, Shums Z, Norman GL, Binder W, Fang H, Petri M. The Journal of Rheumatology2013;40(3):282–6. [2] Atsumi T, Ieko M, Bertolaccini ML, et al. Arthritis & Rheumatism2000;43:1982–93. [3] Bertolaccini ML, Sciascia S, Murru V, Garcia-Fernandez C, Sanna G, Khamashta MA. Thrombosis and Haemostasis2013;110:207–13. [4] Pregnolato F, Chighizola CB, Encabo S, et al. Immunologic Research2013;56:432–8. [5] Vlagea A, Gil A, Cuesta MV, et al. Clinical and Applied Thrombosis/Hemostasis2013;19:289–96. Acknowledgements: Special thanks to Susan Hartzler, Cory Blixt, Serena Navitskas, and Diane Meier. Disclosure of Interest: None declared